Peran Kejaksaan Negeri Malang dalam Upaya Pemberantasan Tindak Pidana Narkotika - Putra, Ivan Praditya; Sabrina, Nahdiya; Ghufron, M. (Postgraduate University of Merdeka Malang, 2023)
The Prosecutor's Office, as one of the government institutions that provides public services in terms of law enforcement as an effort to eradicate narcotics, has the task of carrying out prosecution of criminal cases and investigation of certain criminal acts as well as other tasks stipulated by law. This research will examine the role of the prosecutor's office in efforts to eradicate narcotics crimes in the jurisdiction of the Malang Regency District Prosecutor's Office and what are the obstacles in eradicating narcotics crimes in the jurisdiction of the Malang Regency District Prosecutor's Office. The method used in this research is the empirical legal method. The results of this research state that the role of the Prosecutor's Office in eradicating narcotics crimes in the jurisdiction of the Malang Regency District Prosecutor's Office is carried out through penal policy. Then, the obstacles in preventing and eradicating narcotics crimes in the jurisdiction of the Malang Regency District Prosecutor's Office can be viewed from legal factors, law enforcement factors, means and facilities in law enforcement, community factors and cultural factors.